Analisis Lingkungan Kerja Dan Kepemimpinan Terhadap Work Engagement Pada PT. Prima Asia Satya Kota Medan - Abdullah Sinaga , Mahriz; Wakhyuni, Emi (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
This study aims to analyze the influence of work environment and leadership on work engagement of employees at PT. Prima Asia Satya in Medan. The population in this study were all employees of PT. Prima Asia Satya in Medan with a sample of 88 respondents selected by purposive sampling. The data analysis methods used are validity test, reliability test, classic assumption test, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R2). The results show that the work environment and leadership have a positive and significant influence on the work engagement of employees at PT. Prima Asia Satya in Medan. This means that the better the work environment and leadership, the higher the work engagement of employees. This study provides implications for the management of PT. Prima Asia Satya in Medan to increase employee work engagement through improving the work environment and enhancing the leadership abilities of managers. This study can also be used as a reference for further research related to work engagement.